Does Chemotherapy Change Expression of VEGF A&C and MVD in Acute Myeloid Leukemia? - Zohreh Sanaat (International Journal of Hematology-Oncology and Stem Cell Research, 2014)
Introduction: Acute Myeloid Leukemia is a malignant transformation of hematopoietic tissue, bone marrow infiltration of undifferentiated cells known as blasts that interfere with the production of normal cells. Vascular endothelial growth factor (VEGF) is persistently secreted from myeloid cells and high levels can be detected in patients' serum. Methods: Twenty-one AML patients, who were chemotherapy candidates were evaluated in a clinical trial. Serum VEGF was measured by ELISA. VEGFA, VEGFC mRNA and bone marrow MVD were measured in all patients before and after chemotherapy and then all results were analyzed. Results: There were 10 (48%) female and 11(52%) male patients ranged in age from 20 to 60 years, with an average age of 39.5 ±14.1 years. The mean amount of MVD was reduced from 10.8±3.6 before chemotherapy to7.6±3.3 after chemotherapy (P=0.008). VEGF was also reduced from 0.59±0.16 before chemotherapy to 0.24±0.03 after chemotherapy (P=0.005). Gene expression differences for VEGFA mRNA was 4.6±1.4, while it was 120.7±93.2 for VEGFC mRNA, showing the significance only for VEGA mRNA (P=0.02). Conclusion: Regarding reduced angiogenesis, we can conclude that anti-angiogenic preparations can be effective in treatment course of AML in combination with chemotherapy regimen.